FRI0389 First report of anti-mda5 antibodies in a cohort of italian patients with dermatomyositis: clinical and serologic correlations. (23rd January 2014) - Ceribelli, A.; Fredi, M.; Cavazzana, I.; Taraborelli, M.; Tincani, A.; Selmi, C.; Chan, E. K.; Satoh, M.; Franceschini, F.
Abstract : Background: Polymyositis/dermatomyositis (PM/DM) are autoimmune diseases characterized by skin and muscle inflammation, internal organs involvement and presence of myositis-specific antibodies (MSAs). In recent years, new MSAs have been identified in association with specific clinical features, as anti-CADM140/MDA5 (melanoma differentiation-associated gene 5), -TIF1gamma/alpha (p155/140) and -MJ/NXP-2. Among these, anti-MDA5 antibodies are strongly associated with clinically amyopathic DM (CADM), rapidly progressive interstitial lung disease (RPILD), severe skin manifestations and worse prognosis. In most cases, anti-MDA5 antibodies are detected in Eastern Asian (Japan, Korea, and China) cohorts, with the exception of only one American study. Objectives: The aim of our work is to identify anti-MDA5 antibodies and their clinical associations in a cohort of Italian (European Caucasian) patients with PM/DM. Methods: Sera of 79 consecutive adult Italian (European Caucasian) patients with PM/DM were collected in the outpatient clinic of the Rheumatology Unit in Brescia (Spedali Civili) in 2009-2012. The criteria of Bohan and Peter for PM/DM and the criteria of Sontheimer for CADM were used to establish the diagnosis. All MSAa were characterized by immunoprecipitation (IP) of 35 S-methionin radiolabeled K562 (human erythroleukemia) cell extract except anti-MDA5; anti-MDA5 was confirmed by ELISA (recombinant MDA5 protein and 1:250 diluted sera) and immunoprecipitation-Western Blot (IP-WB) using rabbit anti-MDA5 antibodies. Clinical information were obtained from clinical charts. Results: Anti-MDA5 antibodies were identified in 6/79 (8%) PM/DM cases, and they were the second most common specificity after anti-MJ (8/79; 10%); 23% (8/35) DM and 20% (16/79) in the whole PM/DM cohort still did not have known myositis antibodies. Anti-MDA5 was found in 17% (6/35) in DM and 5/6 cases were CADM, indicating strong association between anti-MDA5 and CADM. The clinical features of 6 anti-MDA5 (+) DM cases were analyzed vs 29 anti-MDA5 (-) DM. Compared to anti-MDA5 (-) DM, anti-MDA5 (+) have severe skin disease, mainly represented by skin ulcers (digit pulp/periungual and Gottron's lesions) and heliotrope rash (67% vs 55%). ILD is more common in the anti-MDA5 (+) DM patients (50%) vs anti-MDA5 (-) (14%): two patients underwent cyclophosphamide therapy, and one died due to RPILD. One also developed subcutaneous emphysema with pneumomediastinum. 83% of anti-MDA5 (+) had CADM (vs 17% CADM in anti-MDA5 (-); p=0.004). Only one anti-MDA5 (+) patient had moderate increase of CPK and muscle weakness. No significant association was identified between anti-MDA5 antibodies and other DM symptoms, such as Raynaud's phenomenon, oral ulcers, calcinosis and higher risk of cancer-associated DM. None of anti-MDA5 (+) cases had other MSAs. Conclusions: Our study is the first report on anti-MDA5 antibodies in adult Italian (European Caucasian) patients with PM/DM. Anti-MDA5 antibodies were detected in 8% (6/79) Italian PM/DM, all affected by DM. Anti-MDA5 antibodies are not specific for Asian patients but they are also common in Italian patients with CADM. Disclosure of Interest : None Declared